Transmission Dynamics of Methicillin-Resistant Staphylococcus aureus in Pigs - Crombé, Florence; Argudín, M Ángeles; Vanderhaeghen, Wannes; Hermans, Katleen; Haesebrouck, Freddy; Butaye, Patrick (Frontiers in Microbiology, 2013)
From the mid-2000s on, numerous studies have shown that methicillin-resistant Staphylococcus aureus (MRSA), renowned as human pathogen, has a reservoir in pigs and other livestock. In Europe and North America, clonal complex (CC) 398 appears to be the predominant lineage involved. Especially worrisome is its capacity to contaminate humans in close contact with affected animals. Indeed, the typical multi-resistant phenotype of MRSA CC398 and its observed ability of easily acquiring genetic material suggests that MRSA CC398 strains with an increased virulence potential may emerge, for which few therapeutic options would remain. This questions the need to implement interventions to control the presence and spread of MRSA CC398 among pigs. MRSA CC398 shows a high but not fully understood transmission potential in the pig population and is able to persist within that population. Although direct contact is probably the main route for MRSA transmission between pigs, also environmental contamination, the presence of other livestock, the herd size and farm management are factors that may be involved in the dissemination of MRSA CC398. The current review aims at summarizing the research that has so far been done on the transmission dynamics and risk factors for introduction and persistence of MRSA CC398 in farms.